Embryology of the Abdominal Wall and Associated Malformations—A Review - Pechriggl, Elisabeth; Blumer, Michael; Tubbs, R. Shane; Olewnik, Łukasz; Konschake, Marko; Fortélny, René; Stofferin, Hannes; Honis, Hanne Rose; Quinones, Sara; Maranillo, Eva; Sanudo, José (Frontiers in Surgery, 2022)
In humans, the incidence of congenital defects of the intraembryonic celom and its associated structures has increased over recent decades. Surgical treatment of abdominal and diaphragmatic malformations resulting in congenital hernia requires deep knowledge of ventral body closure and the separation of the primary body cavities during embryogenesis. The correct development of both structures requires the coordinated and fine-tuned synergy of different anlagen, including a set of molecules governing those processes. They have mainly been investigated in a range of vertebrate species (e.g., mouse, birds, and fish), but studies of embryogenesis in humans are rather rare because samples are seldom available. Therefore, we have to deal with a large body of conflicting data concerning the formation of the abdominal wall and the etiology of diaphragmatic defects. This review summarizes the current state of knowledge and focuses on the histological and molecular events leading to the establishment of the abdominal and thoracic cavities in several vertebrate species. In chronological order, we start with the onset of gastrulation, continue with the establishment of the three-dimensional body shape, and end with the partition of body cavities. We also discuss well-known human etiologies.